2019
DOI: 10.3390/min9070416
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics of Dolomitic Phosphorite Containing Rare Earth Elements and Its Weathered Ore

Abstract: In order to provide a good theoretical guidance for the development and utilization of weathered phosphorite resources, we investigated the geochemical and mineralogical characteristics of primary and weathered phosphorites. The analysis of trace elements showed that the primary ore has hydrothermal sedimentation effect in the later stage, the weathered ore has obvious residual enrichment and the phosphate ore belongs to clastic lithologic phosphate rock. In addition, through leaching test method, it was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Phosphorite is a nonmetallic mineral, which is an important raw material for many kinds of phosphorus products [1][2][3][4][5]. The main types of phosphorite are magmatic apatite, sedimentary metamorphic apatite, and sedimentary rock-type apatite.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorite is a nonmetallic mineral, which is an important raw material for many kinds of phosphorus products [1][2][3][4][5]. The main types of phosphorite are magmatic apatite, sedimentary metamorphic apatite, and sedimentary rock-type apatite.…”
Section: Introductionmentioning
confidence: 99%
“…However, current researches indicated that the REE-bearing phosphates are richer in lanthanum (La), cerium (Ce), neodymium (Nd) and yttrium (Y) [8,9]. For example, for the Zhijin Xinhua rare earth phosphate deposits in western China (the largest rare earth resources reserve of phosphate rock [10]), the average grade of rare earth oxide (REO) is 0.05% to 0.13%, and La, Ce, Nd and Y account for 81.20% of the total REOs [11]. Test data [12,13] showed that REEs replace calcium mainly in the form of isomorphism in the phosphate rock (mainly fluorapatite or carbonate-fluorapatite).…”
Section: Introductionmentioning
confidence: 99%
“…Apatite, allanite, monazite, pyrochlore, and gypsum were identified as the main REE-bearing phases in the different studied samples. Li et al [6] investigated the geochemical and mineralogical characteristics of primary and weathered dolomitic phosphorites containing REEs from the Zhijin mining district in Guizhou Province, China. Novel polymer and chemical products were also used to recover REEs from acidic extracts of Florida phosphate mining materials [7].…”
mentioning
confidence: 99%